SHARIA’S ECONOMIC LAW PERSPECTIVE ABOUT CASH WAQF IN THE ERA OF THE INDUSTRIAL REVOLUTION FOUR POINTS ZERO - Ahyani, Hisam; Muharir; Mahfud, Muntaha (Universitas Islam Indonesia, 2021)
This study aims to determine cash waqf in the view of sharia economic law in the era of the industrial revolution 4.0. The understanding of the Indonesian people regarding cash waqf is still minimal even though this waqf has excellent potential for the welfare of the Indonesian people. Regarding research from the perspective of Islamic economic law on cash waqf in the era of the industrial revolution 4.0, no one has researched it. The method used is literature research, qualitative, with statutory, historical, comparative, and conceptual approaches, and this research is normative. The view of Shariah economics in Indonesia regarding cash waqf is carried out by Law No.41 / 2004 concerning waqf in which moving objects are in the form of “movable object waqf” which is manifested in the form of money. Waqf money in Indonesia in the era of the Industrial Revolution 4.0 can prosper the economy of the people and the country. Waqf is positioned as social worship, wherewith waqf in Law no.41 / 2004 concerning waqf article 1 it is explained that waqf is the act of a wakif to separate or give up part of his property to be used forever for worship purposes and for welfare purposes according to Islamic sharia.